Mars, Incorporated : Skittles becomes part of a controversial shooting - Boylan, Matthew; Gibilisco, Joseph; McCallum, Douglas; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In 2012, a shooting in Florida rose to national prominence after it was revealed that no charges would be pressed against the 28-year-old man who shot and killed an unarmed teenager who was carrying a bag of Skittles candies at the time of his death. The brand became a central symbol of the controversy as discussions about the shooting grew on social media and protests arose throughout the country.
Originally published in Boylan, M., Gibilisco, J., McCallum, D., & ORourke, J. S. (2015). Mars, Incorporated: Skittles becomes part of a controversial shooting. 15-06. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mars, Incorporated; Brand name products; Branding (Marketing); Murder -- Florida